Global banks on trial U.S. prosecutions and the remaking of international finance - Verdier, Pierre-Hugues (Oxford University Press, 2020)
In the years since the 2008 financial crisis, U.S. federal prosecutors have brought dozens of criminal cases against the world's most powerful banks, charging them with manipulating financial indices, helping their customers evade taxes, evading sanctions, and laundering money. To settle these cases, global banks like UBS, Barclays, HSBC and BNP Paribas paid tens of billions of dollars in fines. They also agreed to extensive internal reforms, hiring hundreds of compliance officers, spending billions on new systems, and installing independent corporate monitors. In effect, they agreed to become worldwide enforcers of U.S. law and policies, including financial sanctions-sometimes despite their own governments' protests. This book examines the U.S. enforcement campaign against global banks across four areas: benchmark manipulation, tax evasion, sanctions violations, and sovereign debt. It shows that U.S. prosecutors have unilaterally carved out a new role as global bank regulators, heralding a fundamental shift in how international finance is overseen. Their ability to do so stems from U.S. control over vital hubs of the international financial system, from which they can threaten global banks with exclusion. In some areas, these unilateral U.S. actions have ushered in important multilateral reforms, such as the rise of automatic tax information exchange and better-regulated financial indices. In other areas, such as financial sanctions, unilateralism has attracted protests from other states and attempts to bypass U.S.-based financial infrastructure, which could undermine the country's power."--